2021
DOI: 10.1152/advan.00234.2020
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationships between medical students’ preferred online instructional strategies, course difficulty level, learning performance, and effectiveness

Abstract: Students’ preferences and engagement with online educational resources and activities are crucial for academic success in the context of online medical education. This study investigated the preferences of Chinese medical students regarding the teaching strategies used by instructors and their relationship with course difficulty level, student’s academic performance, and perceived effectiveness. Survey data ( n = 375) were collected from the medical students from one of the largest medical schools in Southern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…For medical courses, however, online learning might be more suitable for students in the pre-clerkship phases compared to students in the clerkship phase. While clinical reasoning and approach to clinical problems can be taught via online media, teaching of physical examination skills and procedures requires direct contact with patients (30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…For medical courses, however, online learning might be more suitable for students in the pre-clerkship phases compared to students in the clerkship phase. While clinical reasoning and approach to clinical problems can be taught via online media, teaching of physical examination skills and procedures requires direct contact with patients (30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“… To analyze the effect of student achievement before and during the Covid pandemic Single Medical School Undergraduate Second year students who took the CVS final unit exam in the previous academic year (n = 183) and during the pandemic (n = 195) Pre and during COVID-19 pandemic Self-reported academic performance There is no difference in student achievement between the pandemic year and the previous year. Cheng et al, 38 2021, China, Cross-sectional Study. To analyze the relationship between medical students’ preferences regarding the teaching strategies used by instructors with the level of course difficulty, students’ academic performance, and perceived effectiveness.…”
Section: Resultsmentioning
confidence: 99%
“…The measurement of academic performance in this scoping varies greatly (see Table 2). There were six studies using GPA [18][19][20][21][22][23] ; nine studies using module scores [24][25][26][27][28][29][30][31][32] ; three studies implementing summative exam scores; [33][34][35] making use of practice/performance exams 2,36 ; two studies employing self-reported academic performance scores 37,38 ; and two studies applying laboratory examination scores. 39,40 Primary Outcome: Academic Performance in Medical Education Before and During the COVID-19 Pandemic…”
Section: Instruments To Measure Academic Performancementioning
confidence: 99%
See 2 more Smart Citations